Analyzing the Impact of Pricing, Promotions, and Customer Experience on Purchase Decisions: A Case Study of Birth Control Pill Sales by a Pharmaceutical Company in Palembang - Rahayu Ningtyas; Efan Elpanso (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The business sector is undergoing significant expansion, compelling enterprises to compete fiercely. Presently, purchase decisions are impacted not only by the quality of the product or service but also by Price, advertising, and experience. This study seeks to assess the impact of pricing, promotion, and experience on Andalan KB PIL's purchasing decisions at a Palembang pharmaceutical company. This research employs a quantitative methodology. The sample population comprises multiple pharmacies distributing Andalan KB PIL at a pharmaceutical company in Palembang. Consequently, 30 samples were acquired that satisfied the criterion. Data analysis employing statistical tools, specifically the SPSS Version 26 application. The study's results indicated that Price did not exert a positive and significant partial effect on purchase decisions, with a significance value of 0.001 (<0.005) and a computed t value of 0.741 (<1.699). Promotion does not exert a positive and significant partial effect on purchasing decisions, evidenced by a significance value of 0.000 (<0.005) and a t-count value of 0.906 (<1.699). The Experience variable does not significantly influence purchase decisions, evidenced by a significance value of 0.000 (less than 0.005) and a t-count value of 0.726 (less than the t-table value of 1.699). The significance at 5% with df1 = 3 and df2 = 26 yielded an F-table value of 3.315. Since the F-count exceeds the F-table and the significance value is 0.000, which is less than 0.005, it can be stated that the variables of Price, promotion, and experience collectively exert a substantial influence on purchasing decisions.